ANALYSIS OF HEALTH EDUCATION SESSION ON FAMILY DEVELOPMENT WITH STUNTING IN PANGKAJENE AND ISLANDS REGENCY, INDONESIA: A CROSS-SECTIONAL STUDY - Mardhatillah; Sulaiman, Zulkarnain; Febrianti, Devy; Said, Sunandar; Ramlan, Pratiwi (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Stunting is a growth disorder experienced by young people whose length or height is not appropriate to their age according to the standards set by the WHO. UNICEF data for 2018 showed that almost 3 out of 10 young children have stunts or are too short for their age. Pangkajene and the Islands Regency showed a stunting prevalence of 29.10% or the highest in South Sulawesi Province in 2018. The Hope Family Program (PKH) is a conditional social assistance program that aims to improve the standard of living of KPM through access to education, health and welfare services as well as reducing the burden of expenditure and increasing the income of poor and vulnerable families. Purpose: To find out the relationship between Family Development Session health education and stunting incidents in Family Hope Program recipients in Pangkajene and the Islands regency. Methods: This study used an observational research approach with a crosectional model. The data was collected using a questionnaire with Family Development Session variables, food management pattern and BBLR history. The data collected was then analyzed using chi-square analysis. Results: Out of 71 respondents who came from recipients of the Hope Family Program, 36 children (51%) suffered stunting and 35 children (49%) did not. Conclusion: There is a significant link between health education Family Development Session, food management pattern and LBW history with stunting incidents in Pangkajene and the Islands Regency (p < 0.05).